An experience and first results of complex biogeocenological studies in dark coniferous forests in the south of the taiga zone of Western Siberia - A. G. Dyukarev; S. G. Kopysov; S. A. Krivets; E. N. Pats; N. A. Chernova (Сибирский лесной журнал, 2024)
In the indigenous southern taiga fern-forb fir forests on the Tom-Yaya interfluve (Tomsk Oblast), the characteristics of tree stands, underbrush, undergrowth, coarse woody debris, ground cover, soils and their contribution to carbon sequestration were studied. The average stock of the forest stand for the type of biogeocenosis was 315.8 ± 56.1 m3 /ha, the average stock of the Siberian fir (Abies sibirica Ledeb.) in different stands varied from 99.2 to 201.4 m3 /ha. In terms of forest health condition, the forest stands are weakened to varying degrees, the fir elements of the forest stands are stronger, which is largely due to their damage by the invasive four-eyed fir bark beetle (Polygraphus proximus Blandford). The underbrush is sparse or of medium density (880–2720 pieces/ha), formed mainly by red raspberry (Rubus idaeus L.) and rowan (Sorbus sibirica Hedl.). Undergrowth with an absolute predominance of fir, its number (800–920 trees/ha) characterizes unsatisfactory regeneration in all studied stands. The average volume of deadfall for the type of biogeocenosis was 2.1 ± 0.5 m3 /ha, stumps 3.3 ± 0.8 m3 /ha, brushwood – 9.2 ± 5.3 m3 /ha. The features of the phytocenosis include high values of floristic diversity (131 species), species richness of the grass cover (105 species) and species richness of plant communities (57 species per 400 m2 ). The increased participation of ferns in the composition of the grass stand is due to the presence of windows occupying from 5 to 30 % of the area of the phytocenosis, formed in stands at the site of fallouts and dead trees, mainly due to the drying out of fir damaged by the four-eyed fir bark beetle.. For the first time, data have been obtained on the phytomass of the ground cover of southern taiga fir forests in Western Siberia, estimated on average at 0.88 t/ha, with a wide variation of this indicator due to the peculiarities of the horizontal structure of the ground cover and different illumination in sub canopy parcels and windows. The features of the composition, structure and thermal regime of the soils of the studied biogeocenoses are shown. Data are presented on changes in the productivity of phytocenoses, soil humus and carbon reserves in various components of the studied forests.